Perioperative use of nonsteroidal anti-inflammatory drugs and the risk of anastomotic failure in emergency general surgery. Issue 4 (October 2017) - Haddad, Nadeem N.; Bruns, Brandon R.; Enniss, Toby M.; Turay, David; Sakran, Joseph V.; Fathalizadeh, Alisan; Arnold, Kristen; Murry, Jason S.; Carrick, Matthew M.; Hernandez, Matthew C.; Lauerman, Margaret H.; Choudhry, Asad J.; et al.
Abstract : BACKGROUND: Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used analgesic and anti-inflammatory adjuncts. Nonsteroidal anti-inflammatory drug administration may potentially increase the risk of postoperative gastrointestinal anastomotic failure (AF). We aim to determine if perioperative NSAID utilization influences gastrointestinal AF in emergency general surgery (EGS) patients undergoing gastrointestinal resection and anastomosis. METHODS: Post hoc analysis of a multi-institutional prospectively collected database was performed. Anastomotic failure was defined as the occurrence of a dehiscence/leak, fistula, or abscess. Patients using NSAIDs were compared with those without. Summary, univariate, and multivariable analyses were performed. RESULTS: Five hundred thirty-three patients met inclusion criteria with a mean (±SD) age of 60 ± 17.5 years, 53% men. Forty-six percent (n = 244) of the patients were using perioperative NSAIDs. Gastrointestinal AF rate between NSAID and no NSAID was 13.9% versus 10.7% ( p = 0.26). No differences existed between groups with respect to perioperative steroid use (16.8% vs. 13.8%; p = 0.34) or mortality (7.39% vs. 6.92%, p = 0.84). Multivariable analysis demonstrated that perioperative corticosteroid (odds ratio, 2.28; 95% confidence interval, 1.04–4.81) use and the presence of a colocolonic or colorectal anastomoses were independently associated with AF. A subset analysis of the NSAIDs cohort demonstrated an increased AF rate in colocolonic or colorectal anastomosis compared with enteroenteric or enterocolonic anastomoses (30.0% vs. 13.0%; p = 0.03). CONCLUSION: Perioperative NSAID utilization appears to be safe in EGS patients undergoing small-bowel resection and anastomosis. Nonsteroidal anti-inflammatory drug administration should be used cautiously in EGS patients with colon or rectal anastomoses. Future randomized trials should validate the effects of perioperative NSAIDs use on AF. LEVEL OF EVIDENCE: Therapeutic study, level III.